THE TURNEY LETTERS: LINGUISTIC EVIDENCE OF FRAUDULENT AUTHORSHIP - BELL, Roger Thomas (Comparative Legilinguistics, 2017)
During the 23rd March - 4th April 2007 crisis over the detention of British military personnel by the Iranian authorities, press interest in the UK centred 1) on the “truth” of the Iranian assertion that the British boats had illegally entered Iranian waters and 2) on the authenticity of the statements the captives made on Iranian television and in the letters written by one of them: Faye Turney, the only woman in the group. It is the purpose of this paper, admittedly after the event, to introduce some linguistic input into the debate on the authenticity of the texts by searching in the letters themselves for evidence of idiosyncratic usages which appear to be non-native and, from those, infer the existence of a covert author, distinct from the overt writer. This paper is, therefore, a short forensic linguistic case study which demonstrates the hypothesis that the texts are corrupt, with a non-native, covert author - almost certainly a Farsi speaker – fraudulently claiming to be both the writer and the originator of the letters.